2014
DOI: 10.4238/2014.december.12.4
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of whether the ACE gene I/D polymorphism constitutes a risk factor for chronic obstructive pulmonary disease in the Turkish population

Abstract: ABSTRACT. Chronic obstructive pulmonary disease (COPD) is characterized by progressive airflow obstruction that occurs as a result of the normal inflammatory process to protect against harmful irritants and chemicals. Another physiological regulatory process, the renin angiotensin system (RAS), plays an important role in the pathology of many diseases. Angiotensin converting enzyme (ACE) is a key enzyme of RAS. We investigated the frequency of the ACE gene I/D polymorphism in patients with COPD in Turkey. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
0
10
0
Order By: Relevance
“…Briefly, the meta-analysis in the present study was performed with fourteen articles [1316, 26–35]. After pooling all data, these 14 articles included 977 patients with COPD and 1,092 control subjects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Briefly, the meta-analysis in the present study was performed with fourteen articles [1316, 26–35]. After pooling all data, these 14 articles included 977 patients with COPD and 1,092 control subjects.…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, the deletion polymorphism, the D allele, of the ACE gene is associated with a higher ACE activity [20], and an elevation of the ACE activity was observed in COPD patients [43]. Therefore, the associations between ACE polymorphism and COPD have been investigated in many previous studies [1316, 26, 28, 31, 44, 45]. However, the results of previous studies regarding the association between ACE polymorphism and COPD were conflicting and contradictory.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ACE gene DD genotype is thought to be associated with an increased risk of rheumatic heart disease in the Saudi population (Al-Harbi et al, 2015), with nitric oxide metabolite levels and systolic blood pressure in clinically healthy Mexican men (no effect in women) (Avila-Vanzzini et al, 2015), with high altitude pulmonary edema in an Indian population (Bhagi et al, 2015), with sepsis susceptibility in Chinese patients (Yang and Zhou, 2015), with periodontal disease susceptibility in a Korean population (Kang et al, 2015), and with cancer risk in Caucasians (Zhang et al, 2014). It has been suggested that ACE gene I/D polymorphism is a genetic risk factor for Alzheimer's disease in a Chinese population (Yuan et al, 2015), while there is reportedly no association between ACE I/D gene polymorphism and a number of conditions and associated risks including type 1 diabetic nephropathy (T1DN) susceptibility and the risk of patients with type 1 diabetes mellitus developing T1DN in a Caucasian population , chronic obstructive pulmonary disease (Ayada et al, 2014) and retinal vein occlusion (Kutlutürk et al, 2014) in a Turkish population, as well as type 2 diabetic nephropathy (T2DN) susceptibility and the risk of patients with type 2 diabetes mellitus developing T2DN in Caucasian populations . In a meta-analysis by Song and Lee (2014), no association was observed between ACE gene I/D polymorphism and the susceptibility to systemic sclerosis in four European studies and one study each in Asian, African American, and Latin American populations comprising a total of 837 cases and 754 controls.…”
Section: Discussionmentioning
confidence: 99%
“…When adverse genetic and external factors combine, a disease is formed (13). The relationship between the polymorphism of the gene encoding angiotensin-converting enzyme (ACE) and COPD has been addressed in numerous prior studies; however, these studies have yielded ambivalent results (14)(15)(16). Prior studies have demonstrated the role of genetic factors in susceptibility to COPD; in part, susceptibility to COPD was found to be associated with polymorphism of proteinaseactivated receptor-1 (17), plasminogen activator inhibitor-1 (18) and b2-adrenergic receptors (19).…”
mentioning
confidence: 99%